A realistic skeletal mechanism for the oxidation of biodiesel surrogate composed of long carbon chain and polyunsaturated compounds. (1st April 2021) - Wu, Gang; Wang, Xin; Abubakar, Shitu; Li, Yuqiang; Liu, Zhiqiang
Highlights: Five components were selected as the surrogate of biodiesel. A realistic skeletal mechanism for the oxidation of biodiesel surrogate was constructed. The mechanism was validated against 0D ignition delay and 3D engine combustion. Combustion characteristics of biodiesel were well predicted by the mechanism. Abstract: To obtain a realistic reduced reaction model for the combustion of biodiesel in compression ignition engine, the heavy methyl esters with long carbon chain and polyunsaturated degree were used to characterize real biodiesel fuel in this study. Methyl palmitate (MHD), methyl stearate (MOD), methyl linoleate (MOD9D12D), methyl–5–decenoate (MD5D) and n –decane were selected as the surrogate of biodiesel. A skeletal mechanism with 187 species and 982 reactions was developed for the oxidation of biodiesel surrogate using the decoupling methodology. The mechanism was partitioned into three, including the relatively simplified fuel–related sub-mechanism, the ester group–related sub–mechanism, and the detailed core sub–mechanism during the construction process. It was validated by zero–dimensional ignition delay for each component in biodiesel surrogate under variable conditions. The predicted outcomes are in concordance with the experimental information, which preliminarily verifies the effectiveness and accuracy of the mechanism. A three–dimensional computational fluid dynamics code coupled with the mechanism was subsequently utilized to simulate engine combustion. The findings show that the combustion characteristics of biodiesel are robustly replicated, portraying that the newly developed biodiesel mechanism can be assuredly used in the practical engine simulation.